Analisis Kestabilan Lereng Highwall Seam C Pada Area Pit B Tambang Batubara PT. Mifa Bersaudara Kabupaten Aceh Barat, Provinsi Aceh - Muhamad Anton Nugroho; Supandi; Bayurohman Pangacella Putra (Retii, 2023)
PT Mifa Bersaudara is a mining company that mines coal commodities, this company operates in West Aceh, Aceh Province. The mining system used is an open pit mining system with a downward mining direction. On March 16, 2021 the main IPD slope of seam C has experienced a landslide at RL 40 to the lowest radius level of RL 25 where the location of the slide is above the highwall seam C slope which is feared to affect the mining process carried out because of the analysis of the condition of the highwall seam C slope also experienced extreme weathering with saturated rock conditions. Based on the results of the analysis carried out during the initial geotechnical exploration of the 2014 Final Report Geotechnical and Hydrogeological Study for MBD Coal Mine at Drill point GT 05 and section J, the specific gravity values of coal 1 and coal 2 = 14 kN/m3, sandstone = 22 kN/m3 , mudstone 1 and mudstone 2 = 23 kN/m3, mudstone 3 = 22 kN/m3. Assuming the rock strength is coal 1 = 4500 kPa, coal 2 = 6000 kPa, sandstone = 700 kPa, mudstone 1 = 800 kPa, mudstone 2 = 2000 kPa, mudstone 3 = 5000 kPa. Whereas the value of the internal friction angle is 0 ͦ which is accompanied by a slope model and its constituent materials, but the attached data is not right at the location where the slide occurred and must be re-validated through several approaches to obtain the embankment stratigraphy and material property values that coincide at the location of the landslide. Based on field validation, it shows changes in material properties and stratigraphy on the slopes with FK = 1.376 and the results of back analysis data show FK = 0.835 with changes in material properties that can affect the safety factor of the slope. The results of the evaluation data are based on entering the parameters from the results of back analysis and incisions after the landslide, so FK = 1,000